Vegetative Propagation of Rhododendron arboreum Sm. Using FRI-wire Technique - Ahmad, Peerzada Ishtiyak; Puni, Lokho (Indian Forester, 2010)
Vegetative propagation of R. arboreum was carried out successfully using FRI-Wire technique and root inducing hormones (IAA and NAA at the concentrations of 1000 ppm and 2500 ppm each). IAA at 2500 ppm gave highest percentage of rooting (66.66%) in the month of April.